2015
DOI: 10.3310/hta19950
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Long-term Outcomes of NHS Stop Smoking Services (ELONS): a prospective cohort study

Abstract: BackgroundNHS Stop Smoking Services (SSSs) provide free at the point of use treatment for smokers who would like to stop. Since their inception in 1999 they have evolved to offer a variety of support options. Given the changes that have happened in the provision of services and the ongoing need for evidence on effectiveness, the Evaluating Long-term Outcomes for NHS Stop Smoking Services (ELONS) study was commissioned.ObjectivesThe main aim of the study was to explore the factors that determine longer-term abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 88 publications
1
63
0
Order By: Relevance
“…Previous analysis showed that at 1-year follow-up, 38% of patients were biochemically verified abstinent from smoking [24]. These are very high success rates compared for example with around 8% achieved in UK stop smoking services [25] (which also deliver a combination of behavioural support and pharmacotherapy, albeit usually restricted to a shorter period of time ) and compared with the Mayo clinic which uses a similar treatment model and reported 28% self-reported abstinence at 6 months [26].…”
Section: Methods Interventionmentioning
confidence: 99%
“…Previous analysis showed that at 1-year follow-up, 38% of patients were biochemically verified abstinent from smoking [24]. These are very high success rates compared for example with around 8% achieved in UK stop smoking services [25] (which also deliver a combination of behavioural support and pharmacotherapy, albeit usually restricted to a shorter period of time ) and compared with the Mayo clinic which uses a similar treatment model and reported 28% self-reported abstinence at 6 months [26].…”
Section: Methods Interventionmentioning
confidence: 99%
“…105,106 This study employed a similar research design to the 2005 research [99][100][101] but involved more areas of the country and a larger sample of service clients. It found that overall abstinence rates from smoking had dropped from 15% to 8% at 52 weeks but that smokers who received the best combination of stop smoking medication and behavioural support delivered by trained specialists were two to three times more likely to quit than other clients.…”
Section: Development Of Stop Smoking Servicesmentioning
confidence: 99%
“…It found that overall abstinence rates from smoking had dropped from 15% to 8% at 52 weeks but that smokers who received the best combination of stop smoking medication and behavioural support delivered by trained specialists were two to three times more likely to quit than other clients. 105,106 Stop Smoking Services for pregnant women The UK's SSSs began to develop tailored provision for pregnant women from 2000. This involved the same combination of support developed for the general adult population (a combination of behavioural support and medication, in this case NRT, which is the only product licensed for use in pregnancy).…”
Section: Development Of Stop Smoking Servicesmentioning
confidence: 99%
“…An added benefit of group treatments is that the successful quitter can assist and give confidence to other smokers trying to quit, which also helps the former smoker stay quit. This may be one explanation for why some studies show that group counseling is more effective than individual counseling for quitting smoking [55].…”
Section: Box 1 Case Example -Thomas and Jennifermentioning
confidence: 99%